Selected instruments of stimulating innovative activity and transfer of technology - Sporek, Tadeusz (Publishing House of the Wrocław University of Economics, 2009)
The authors of the growth theories which are called “endogenous” [Verspagen, Wakelin 1997, p. 183] theories stress that development based on know-how1 and technical innovations, not on capital accumulation, is the driving force of economy [Green Paper… 1995, p. 10; Kotler et al. 1999, p. 32]. Economic growth and technological progress which it implies constitute a process of continuous transformation, not a single adjustment to a long-term way of increase [Verspagen 2001, p. 24]. This transformation is possible mainly due to radical technical innovations which are determined mainly by efficient operation of high-tech sector and lead to structural changes [Verspagen 2001, p. 18]. Constraints of high technological development should not be sought in the access to natural sources, but in “creation” and utilising scientific knowledge and specialist skills [Christidis et al. (eds.) 2002, p. 38]. Therefore, investing in knowledge understood in its broad sense, especially in the fields such as ICT, biotechnologies or nanotechnologies, which are key fields for the operation of contemporary and future economy, is needed [Christidis et al. (eds.) 2002, p. 184]. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 407-416